Noxious Housing: The Influence of Single Room Occupancy (SRO) Facilities on Neighborhood Crime - Krupa, Julie M. (Crime & delinquency, 2021)
Certain establishments (e.g., alcohol outlets or pawnshops) attract or generate crime because they operate with little oversight and are often located in poor or disordered neighborhoods. Single room occupancy (SRO) facilities share some of these characteristics. SROs tend to be rundown motels or apartment buildings that offer affordable housing for low-income clientele. It is likely that SROs also generate and attract criminal activity that affects the neighborhood. Using police incident report data for St. Petersburg, FL, this study examines the impact of SROs on violent, property, and nuisance crimes at the neighborhood level. Negative binomial regression models suggest that the presence of an SRO in the focal or nearby neighborhood increases local crime, with the impact varying by crime type.